Severity of Growing Pain in Children and its Association with Vitamin D: A Tertiary Hospital Study (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background:  Growing pain (GP) is the most common form of nonspecific, recurrent leg pain in children. Some studies have found an association of vitamin-D with the severity of GP and observed remarkable pain improvement after vitamin D supplementation.Objectives: To assess the severity of GP and serum level of vitamin D in children and to determine the association between them.Methods: This cross-sectional study was conducted in the Department of Paediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU). Seventy children between 6-12 years were included in the study from March 2020 to August 2021. Children who fulfilled the Evans criteria of GP were enrolled  and severity of GP was assessed by Wong- Baker Facies Scale in this study. Serum 25-hydroxy-vitamin-D [25(OH)D] levels were measured and subsequently their association with the severity of growing pain were determined.Results: In this study, 97.14% of growing pain patients had hypovitaminosis D and among them majority (87.14%) were vitamin D deficient. Moderate intensity of pain was found in 51.4% of children followed by severe (30%) and mild (18.6%) intensity of pain. Severity of pain was significantly associated with lower serum levels of vitamin D.Conclusion: It may be concluded that most of the children with GP had hypovitaminosis D and severity of pain significantly increased with the decrement of serum vitamin D level.J Bangladesh Coll Phys Surg 2023; 41(4): 282-286